Relationship between Structural Empowerment of Nurses, Managerial Experience, and Resistance to change: A Cross-sectional Study - Baker, Omar Ghazi (Universitas Airlangga, 2025)
Introduction: Nurses play an integral role in the healthcare system, representing the most essential and prominent component of the healthcare sector. To build a resilient organizational plan, it is necessary to engage employees in decision-making and offer them greater autonomy. This is usually accomplished through empowering employees, with the behavior of leaders playing an integral role, especially in empowering leadership. Thus, this study aimed to examine the relationship between structural empowerment among nurses, years of managerial experience, and resistance to change. Method: This cross-sectional, descriptive correlational survey included 148 participants employed in formal or acting leadership roles such as nursing managers, head nurses, or nursing supervisors in a Riyadh university hospital, selected using convenience sampling. Data were collected using the CWEQ-II and RTC scales. Descriptive statistics, Pearson correlation, ANOVA, and multiple regression were used to analyze the data. Results: The results indicated that structural empowerment among nurses is significantly and negatively associated with resistance to change, indicating that an increase in structural empowerment leads to a decrease in resistance to change. However, years of managerial experience showed no significant association with resistance to change, demonstrating that having more or fewer years of managerial experience did not meaningfully impact resistance levels. Conclusion: This study concluded that with more employment empowerment, exposure, and accessibility to information, resistance to change can be reduced.